Effect of the combination between metformin and lansoprazole on blood glucose levels in diabetic mice - الناصيف آلاء; رنا ماخوس (Latakia University Journal -Medical Sciences Series, 2024)
Several studies have indicated the ability of gastrin to promote an increase of β cell mass in pancreas, an increase of glucagon-like-peptide-1(GLP-1) secretion and therefore that gastrin may improve glucose tolerance. proton pump inhibitors (PPIs) indirectly elevate serum gastrin levels in animals and humans via a negative feedback effect. Therefore, the aim of the study was to investigate the effect of lansoprazole on blood glucose levels in diabetic mice. Hyperglycemia was induced experimentally in female white albino mice by a single intraperitoneal administration of alloxan monohydrate which dissolved in normal saline. Seven days later, mice with FBG levels ≥150 mg/dL were considered diabetic and used in this study. Mice were allocated to five groups: (normal group), (diabetic group), (DM+lansoprazole group), (DM+metformin group), (DM+Combination group). Fasting blood glucose (FBG) levels and intraperitoneal glucose tolerance test (IPGTT) were determined at the end of the study. LPZ significantly improved glucose metabolism compared with diabetic control group. We found that metformin and lansoprazole were equally effective in reducing FBG levels. Contrary to our expectation, the effects of the combination therapy and metformin mono-therapy on glycemic control were equivalent.